Croatian learners' motivation - Mihaljević Djigunović, Jelena (1998)
The article first discusses several models of motivation, followed by the author's own research model used to investigate Croatian learners' motivation for EFL learning. The comprehensive exploratory study described here resulted in identifying three types of motivation (pragmatic-communicative, affective, integrative) and two demotivators (teaching setting and learning difficulties).
Projekt MZOS
ENG